Deaf teachers' experience of being students at the University of the Witwatersrand. - Magongwa, Lucas (My University, 2009)
Due to the specialist nature of their use of a visual language, Deaf and hard of hearing students have unique experiences at institutions of higher education. This research explored the experiences of Deaf teachers as students at Wits University. I employed a qualitative research design in the study. In -depth interviews and documentary information were used to collect data from twelve current and past Deaf and hard of hearing students. Current theory, practice and legislation designed to guide the creation of an inclusive education society were examined in order to explore the implications they have for Deaf students in terms of inclusion and access to education. The findings showed high level of academic competitiveness among the Deaf and hard of hearing students but low social participation. Their academic success was driven by factors such as commitment to Deaf education, the availability of interpreting services, having Deaf peers and their pre-university experiences.
Keywords: Deaf; Hard of hearing; South African sign language; Higher education institutions; Teacher education; Inclusion; Support services; Integrative experiences; Interpreters; Profound deafness